2012
DOI: 10.1093/infdis/jis470
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind Placebo Controlled Trial of Balapiravir, a Polymerase Inhibitor, in Adult Dengue Patients

Abstract: Background. Dengue is the most common arboviral infection of humans. There are currently no specific treatments for dengue. Balapiravir is a prodrug of a nucleoside analogue (called R1479) and an inhibitor of hepatitis C virus replication in vivo.Methods. We conducted in vitro experiments to determine the potency of balapiravir against dengue viruses and then an exploratory, dose-escalating, randomized placebo-controlled trial in adult male patients with dengue with <48 hours of fever.Results. The clinical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
188
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(192 citation statements)
references
References 15 publications
3
188
0
1
Order By: Relevance
“…The use of the reduction of serum viremia as the primary laboratory endpoint for evaluating therapeutics against DF failed to show any significant efficacy, as recent clinical trials of repurposed drugs have demonstrated (10,(39)(40)(41)(42). Moreover, the potency of the tested drugs has been significantly questioned, since analysis showed an almost 4-log reduction in viral load during the acute phase for both the treated and untreated arms (10,(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the reduction of serum viremia as the primary laboratory endpoint for evaluating therapeutics against DF failed to show any significant efficacy, as recent clinical trials of repurposed drugs have demonstrated (10,(39)(40)(41)(42). Moreover, the potency of the tested drugs has been significantly questioned, since analysis showed an almost 4-log reduction in viral load during the acute phase for both the treated and untreated arms (10,(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the potency of the tested drugs has been significantly questioned, since analysis showed an almost 4-log reduction in viral load during the acute phase for both the treated and untreated arms (10,(39)(40)(41)(42). Viremia clearance is associated with the immune status of the patients and virus serotype (39,43).…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, the current compound has provided an opportunity to answer two paramount questions for dengue therapeutics development: can an antiviral drug reduce viremia in dengue patients (infected with DENV-2 or -3), and, if so, will viremia reduction prevent patients from developing severe hemorrhagic fever and shock? Since compound 14a is not a prodrug and directly inhibits viral NS4B, it is expected to eliminate the complications of nucleoside inhibitors (which require host kinases to convert them to their triphosphate forms before being antiviral active), as evidenced by the efficacy failure of balapiravir in dengue patients (6,33).…”
Section: Discussionmentioning
confidence: 99%
“…The longer duration of fever in patients with primary dengue may make this group of patients more suitable for enrollment into therapeutic trials in which the duration of fever is a primary outcome. 33,34 The more rapid fever clearance in secondary infection may require a larger cohort of patients to observe a statistically significant reduction in fever duration. 35 This necessity not only increases cost but also the number of patients exposed to an investigational compound, and its safety profile remains to be fully determined.…”
Section: Discussionmentioning
confidence: 99%